The reality of secondary education for girls in the Wadi Araba district for the years (2014- 2018) of the attention of administrators and teachers - Alhayawat, Hanan Salam Hassan (Journal of Educational and Psychological Sciences, 2020)
The present study aimed to reveal the reality of secondary education in the Wadi Arab district from the point of view of administrators and teachers. To achieve the study objective, the researcher used the descriptive method. The results of the study showed that the total degree of administrative and technical level from the point of view of teachers and administrators achieved an average level, with an average of (2.73) and a percentage of (55%). At the level of domains, the administrative field got an average of 2.98, while the technical field got an average of 2.48 Delusional grade (average). There are statistically significant differences between the technical level and the administrative level. In light of the results, a set of recommendations and suggestions were made to improve secondary education in Wadi Araba district administratively and technically.
Keywords: reality; Secondary education; Wadi Araba; administration and teachers